Digitalisasi Pengelolaan Pustaka Sekolah - Dafwen Toresa; Taslim; Susi Handayani; Edriyansyah; Rometdo Muzawi (SATIN - Sains dan Teknologi Informasi, 2023)
Along with the development of science and the globalization of information that demands the creation of an all-computerized state. At SMA Negeri 4 Tualang, Siak Regency, the process of processing library data to making reports still uses manual bookkeeping. This can cause the process of searching for book data, member data and book borrowing data to take a long time and not to mention if the data is lost so it cannot be used again. Library applications are made according to user needs using the PHP programming language with MySQL database storage and Waterfall modeling. This library application has been tested with the black box method with 100% results then implemented and measured with values and measuring indicators as follows: User Satisfaction = 94%, Data Accuracy = 93%, Speed and convenience = 96%, Application and information security = 93 % and Support = 96%. Thus the digitization of library management is very beneficial for library managers and students as users at SMAN 4 Tualang